Recent advances of microwave-assisted deep eutectic solvent for lignocellulosic biorefining - Zhou, Jiajiang; Chen, Bingkun; Tong, Li; Chong, Gunhean; Abdullah, Luqman Chuah; Guo, Haixin (Springer Science and Business Media B.V., 2025)
Lignocellulosic biomass (LCB) is a promising renewable feedstock for biofuels and biochemicals. However, its structural complexity, strong lignin-carbohydrate linkages, and high cellulose crystallinity hinder efficient valorization. Deep eutectic solvents (DESs) have emerged as a sustainable pretreatment technology, capable of removing over 90% of lignin and improving enzymatic hydrolysis efficiency to above 95% by modifying biomass composition, enhancing accessibility, and disrupting lignin structures. This review systematically explores the impact of key DES properties—including viscosity, pH, hydrogen bond donor (HBD) and acceptor (HBA) composition, temperature, etc., on biomass fractionation. Special focus is given to microwave-assisted DES (MW-DES) technology, which accelerates biomass deconstruction through localized dielectric heating, significantly reducing pretreatment time from several hours to as little as 40 s while lowering energy consumption. MW-DES further enhances enzymatic digestibility, with microwave-assisted DES pretreatment increasing sugar yields compared to conventional methods. Despite its advantages, MW-DES faces challenges related to high viscosity, heating uniformity, and scalability. Future research should focus on optimizing DES formulations, refining microwave parameters, and integrating MW-DES into continuous biorefinery processes. Additionally, DESs facilitate catalytic sugar valorization, enhancing glucose and fructose conversion into 5-hydroxymethylfurfural (HMF). Addressing these challenges will advance MW-DES as a scalable and sustainable strategy for lignin valorization, cellulose hydrolysis, and bio-based chemical production, supporting a circular bioeconomy.